Review on the enhancement techniques and introduction of an alternate enhancement technique of solar chimney power plant - Aja, Aja; Al-Kayiem, H.; Karim, Z. (Asian Network for Scientific Information, 2011)
Due to the low plant efficiency associated with Solar Chimney Power Plant, there is a need for the plant performance enhancement. This study presents the enhancement techniques of solar chimney power plant. It reviews previous works that had been done in performance enhancement of solar chimney power plants. It also, introduces an alternative approach to enhance the solar chimney performance by hybridizing the solar operation mode and waste heat energy from flue gas. The new idea is to convert the waste thermal energy in the flue to useful thermal energy in a Solar Chimney Power Plant collector. It is another form of waste heat energy recovery and utilization method. © Asian Network for Science Information.